Supplier selection using a hybrid model for 3C industry - Chen, Kwo-Liang; Yeh, Ching-Chiang; Huang, Jo-Chen (Journal of Business Economics and Management, 2014)
Supplier selection is a good strategy for firms that can reduce operating costs and improve competitiveness for computer, communication and consumer electronics (3C) industry. The major aim of this research is to build a systematic approach for establishing a supplier selection model, and then prioritize improvement criteria in order to best supply chain management. The study proposed a hybrid approach by using the interpretive structural modeling (ISM) method to deal with the interrelationship among criteria, and the analytic network process (ANP) method is employed to recognize the criteria of supplier selection and evaluate with respect to environmental competency for the case of Taiwan’s 3C industry. The study shows that the proposed model could be an effective and efficient decision-making tool that can be easily extended to other contexts. Especially, it has provided decision-makers and researchers with better understanding of the differences in supplier selection activity needs and specific management interventions by examining these criteria.